Analysis Of The Implementation Of Product Supply Chain Management At Transmart Cilegon: IMPLEMENTATION OF PRODUCT SUPPLY CHAIN MANAGEMENT - zulkarnain, Rizal; Gunawan, Iba; Noviani, Lona (Universitas Banten Jaya, 2024)
PT. Trans Retal Indonesia is a retail company in Indonesia which has several branch stores in various regions, one of which is the area, especially Cilegon City. PT Transmart Cilegon as a research object using qualitative descriptive research methods. Transmart Cilegon implements inventory management in its supply chain management strategy, resulting in several benefits. Keywords: Supply Chain Management Keywords: Number of Population, Minimum Wage, Open Unemployment.